Analysis of Mudjia Rahardjo's Views: Language Philosophy and Efforts to Preserve Regional Languages - Hidayat, Muhammad Sofian; Hibban, Muhammad Faisal (Universitas Islam Negeri Sumatera Utara, 2024)
The current era of globalization and westernization poses a real threat to the existence of regional languages, one of which is manifested in the single market program agreed upon by ASEAN countries. In line with that, the study of language philosophy has a very important role in cultural preservation, especially regional languages. This article discusses the views of Mudjia Rahardjo, an Indonesian linguist and philosopher, regarding the philosophy of language and efforts to preserve regional languages with the aim of finding a harmonious correlation between the study of the philosophy of language and efforts to preserve regional languages. Through the content analysis method with data sources from the Philosophy of Language lecture material delivered by Mudjia Rahardjo in the Postgraduate class at Darussalam Gontor Ponorogo University. Based on the content analysis of the lecture material on the philosophy of language delivered by Mudjia Rahardjo, the author concludes that there are several correlations that are compatible between the study of the philosophy of language and efforts to preserve the local language. 3. Philosophy of language can provide a philosophical basis for efforts to preserve regional languages